A two-phase single-reciprocating-piston heat conversion engine - Kirmse,C; Oyewunmi,OA; Haslam,AJ; Markides,CN (2015)
This paper considers an energy-conversion heat-engineconcept termed ‘Up-THERM’. This machine is capable ofconverting low- to medium-grade heat to useful positivedisplacementwork through the periodic evaporation andcondensation of a working fluid in an enclosed space. Thesealternating phase-change processes drive sustained oscillations ofthermodynamic properties (pressure, temperature, volume) as theworking fluid undergoes an unsteady thermodynamic heatenginecycle. The resulting oscillatory flow of the working fluidis converted into a unidirectional flow in a hydraulic loadarrangement where power can be extracted from the machine.The engine is described with lumped dynamic modelsconstructed using electrical analogies founded on previouslydeveloped thermoacoustic and thermofluidic principles, whichare extended here to include a description of the phase-changeheat-transfer processes. For some sub-components of the engine,such as the gas spring, valves and the temperature profile in theheat exchangers, deviations from the linear theory are nonnegligible.These are modelled using non-linear descriptions. Inparticular, the results of linear and non-linear descriptions of thegas spring are compared using three important performanceindicators — efficiency, power output and frequency.The non-linear description of the gas spring results in morerealisticpredictions of the oscillation frequency compared todirect measurements on an experimental prototype of a similarengine. Owing to its mode of operation and lack of moving parts,the Up-THERM engine does offer a much simpler and morecost-efficient solution than alternative engines for heat recoveryand solar applications. The results from this work suggest thatthis technology can be a competitive alternative in terms of costper unit power in low-power, small-scale applications, especiallyin remote, off-grid settings, for example in developing countrieswhere minimising upfront costs is crucial.